Comparing Annual and Lifetime Earnings: Distributions and Wage Premiums for a Cohort of Swedish Men - Sandgren, Sofia (Journal of Income Distribution®, 2007)
In this paper I use the Malmö Longitudinal Data set and calculate actual lifetime earnings for the 1928 cohort of Malmö men. I compare distributions of, and the educational wage premiums for, annual and lifetime earnings. The distribution of lifetime earnings is found to be less than the average annual distribution, but not for each separate annual estimate. When comparing annual and lifetime wage premiums, the significance for the lower levels of education tend to disappear. The annual wage premiums seem to be overestimated compared to the lifetime premiums, except for academic studies which are under-estimated annually.